The Implementation of Mind Mapping in Reading Narrative Text for Eight Graders - Rahmadina, Indy; Kurniati, Ruri Fadhilah (Nusantara Educational Review, 2024)
The purpose of this study is to describe the learning process using mind mapping on reading narrative text material and student's perceptions of the use of mind mapping. Data collection was carried out in July 2023 in class VIII-A of Al-Muayyad Middle School Wates Kedensari Tanggulangin and totalled 8 students. This study uses qualitative descriptive research. The instruments used in this study were observation, interviews, and documentation. Researchers used observation techniques to obtain data during the mind-mapping learning process on reading narrative text material in class. Students gave a positive response to the use of mind mapping in class. The results of the interview showed that most students thought that the use of mind mapping could have a positive impact because felt interested in learning and found it easier to understand the material. Tujuan dari penelitian ini adalah mendeskripsikan proses pembelajaran menggunakan mind mapping pada materi reading narrative text dan presepsi siswa terhadap penggunaan mind mapping. Pengambilan data dilakukan pada bulan Juli 2023 di kelas VIII-A SMP Al-Muayyad Wates Kedensari Tanggulangin dan berjumlah 8 siswa. Penelitian ini menggunakan penelitian deskriptif kualitatif, Instrumen yang digunakan dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Peneliti menggunakan teknik observasi untuk memperoleh data pada saat proses pembelajaran mind mapping pada materi reading narrative text dalam kelas. Siswa memberikan respon positif pada penggunaan mind mapping di kelas. Hasil wawancara menunjukan sebagian besar siswa beranggapan bahwa penggunaan mind mapping dapat memberikan dampak positif karena mereka merasa tertarik untuk belajar, dan lebih mudah memahami materi.